Newborn Firms and Regional Diversification Patterns: The Role of Cultural Diversity. (7th August 2020) - Colombelli, Alessandra; D'Ambrosio, Anna; Meliciani, Valentina; Quatraro, Francesco
Abstract: We blend the economics of diversity and evolutionary economic geography theories and study the relationship between the cultural diversity of foreign-born entrepreneurs and regional sectoral diversification, proxied by the sectoral variety of newborn firms. We focus on Italian evidence and use a unique data set that stems from a combination of different sources of information, including the Union of the Chambers of Commerce, the OECD, and the National Institute of Statistics. The results confirm that cultural diversity of entrepreneurs is associated with greater sectoral variety of newborn firms, with an imbalance in favor of variety in unrelated activities vis-à-vis related ones.